Narrativas sobre proyecto vital, apoyo familiar y relaciones con pares en un grupo de jóvenes exfutbolistas - Ninco Toro, Hermes (Universidad Antonio Nariño, 2024)
The present investigation analyzes the Narratives about vital project, family support and relationships with peers in a group of young ex-soccer players. The methodology used is qualitative and narrative design. The participants were five (5) young people whose ages range from 20 to 25 years, from the city of Bogotá, Colombia; who did not have the possibility of being professional soccer players, even being part of their life project. The technique chosen to collect the information was the open interview and the inductive categorization was used for its analysis. The results allowed to explore the experiences and expectations that they had in this event, as well as, they could show it in their family and their environment.